Comparison of the Coronal Green-line Intensities with the EUV Measurements from SDO/AIA. (1st July 2022) - Zhang, Xue-Fei; Liu, Yu; Zhao, Ming-Yu; Liu, Ji-Hong; Elmhamdi, Abouazza; Song, Teng-Fei; Li, Zi-Han; Li, Hong-Bo; Sha, Fei-Yang; Wang, Jing-Xing; Li, Xiao-Bo; Shen, Yuan-Deng; et al.
Abstract: The intensity of the green line (Fe xiv 5303 Å) is the strongest in the visible spectrum of the solar corona, and this line has been used as long-term powerful diagnostic tools for studying the coronal configurations and hot plasma dynamics. However, it remains unclear and an open question whether there exists close relationship between the green line intensities and the coronal extreme ultraviolet (EUV) line emissions for various coronal structures. In this paper, we use the green-line data by the Lijiang YOGIS Lyot coronagraph and the EUV data from the Solar Dynamics Observatory/Atmospheric Imaging Assembly instruments in order to perform direct comparisons and analyses, based on two algorithms developed to extract particular features in the low corona. It is found that, among the correlation coefficients obtained between the intensities of 5303 Å and the EUV lines, the coefficients between the green line and the 211 Å wavelength for different coronal structures and different limb locations always keep the highest values (ranging from 0.89 to 0.99), which has not been reported before. This result can be helpful and promising to link together the various physical processes involved at different heights in the corona by precisely tracking the bright loops or other features observed in 5303 Å above the limb down to the correct surface locations revealed by the 211 Å data. Furthermore, the ground-based observations of the coronal green line and the space-based EUV observations at 211 Å can advantageously complement each other when there is a need.